2003
DOI: 10.1136/thorax.58.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Bronchodilation by an inhaled VPAC2 receptor agonist in patients with stable asthma

Abstract: Background: The synthetic vasoactive intestinal peptide (VIP) analogue Ro 25-1553 is a selective VIP-PACAP type 2 (VPAC 2 ) receptor agonist that causes a bronchodilatory effect in guinea pigs in vivo. The effect of Ro 25-1553 given by inhalation to patients with asthma was studied and compared with that of a long acting β 2 adrenoceptor agonist. Methods: Twenty four patients with moderate stable asthma participated in a double blind, randomised, placebo controlled, crossover study. The primary variable was br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 24 publications
0
40
0
1
Order By: Relevance
“…Because RA appears to be a more rational target disease than OA for the development of antiinflammatory neuropeptides, the use of stable VPAC 2 receptor agonists is an attractive alternative to the use of parenteral short-lived neuropeptides (43). In this regard, the VPAC 2 agonist used in this study (RO25-1553) was recently tested in patients with asthma, without significant toxicity (44).…”
Section: Discussionmentioning
confidence: 99%
“…Because RA appears to be a more rational target disease than OA for the development of antiinflammatory neuropeptides, the use of stable VPAC 2 receptor agonists is an attractive alternative to the use of parenteral short-lived neuropeptides (43). In this regard, the VPAC 2 agonist used in this study (RO25-1553) was recently tested in patients with asthma, without significant toxicity (44).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma VIP level of patients with acute asthmatic exacerbations was found to be significantly lower compared to the controls and showed correlation with the response to therapy, suggesting that bronchodilatory and vasodilatory actions of the peptide are essential in this regard (Cardell et al, 1994;Said, 1982). Even in a human study, VPAC2 receptor was shown to exert inhibitory action against bronchial asthma (Lind en et al, 2003). After conjunctival allergic challenge, VIP was found to be elevated in allergic patients similarly to the lesional skin of patients with atopic dermatitis, indicating an immunomodulatory action of the peptide (Giannetti et al, 1992;Sacchetti et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Vasoactive intestinal peptide analogues and potassium channel openers, i.e. agonists of bitter taste receptors (TAS2Rs), have shown bronchodilator effects [44][45][46]. Unfortunately, these drugs have had more potent vasodilator than bronchodilator effects.…”
Section: New Classes Of Bronchodilator Therapymentioning
confidence: 99%